JIHADWATCH FRAMING OF WORD ISLAM AND MUSLIM: A CASE IN NOVEMBER 2017 - Ahmad Zaidi (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
Jihadwatch.org is a website notorious for its anti-Islam news. However, no study focuses on how the website frames Islam itself. This study focuses on analyzing how Islam and Muslim the people who have Islam as their religion framed in the website. The Corpus approach is chosen in this research. It is chosen as it offers a quantitative approach to the data. This quantitative approach hopefully avoids subjectivity in the analysis. The data was taken in November 2017. Using collocation feature in corpus software, Islam is framed as a radical religion, trying to convert everybody, and the ideology is not suited in the west. Besides that, Muslims are framed as migrants, violent, and cannot accept the western lifestyle. Further research with more extensive data is required for further analysis. The next researcher can also analyze the website in the opposite extreme pro-Islam movement.